Radiation pressure on inhomogeneous active chiral structures with propagation matrix. (1st May 2022) - He, Simin; Wang, Maoyi; Zhang, Shitian; Li, Guiping; Yu, Mengxia; Liu, Yu; Xu, Jun; Wang, Maoyan
Abstract: The propagation matrix method and the Maxwell stress tensor are developed to calculate radiation pressure on an inhomogeneous active chiral structure. Based on boundary conditions, a 4 × 4 propagation matrix connecting two forward and two backward plane waves in adjacent chiral media is derived. This propagation matrix method allows us to access the net, co‐ and cross‐polarized radiation pressure, which are expressed by co‐ and cross‐polarized reflection and transmission coefficients, exerted on magnetoelectric coupling inhomogeneous chiral slabs via the derivation of the Maxwell stress tensor for arbitrary polarized plane waves incidence. The accuracies of the methods are examined using the finite difference time domain method and the Lorentz force densities. The radiation pressure on a homogeneous or inhomogeneous active chiral slab affected by the angle of incidence, thickness, chirality parameter, and polarization states of incident waves are investigated. This work is believed to provide insights for detecting chirality parameters of inhomogeneous materials by optical forces.